Identifikasi dan Karakterisasi Tanaman Pewarna Alam Tenun Pegringsingan Desa Tenganan - IDA AYU PUTRI DARMAWATI; GEDE WIJANA; A.A. MADE ASTININGSIH; IDA AYU MAYUN; NI LUH MADE PRADNYAWATHI (Agrotrop : Journal on Agriculture Science, 2016)
The Characterization and Identification of Plant Natural Dye Tenun PegringsinganTenganan Village. The aim of the research was to know the dyeing process and the kind ofplant dyes are used in the manufacture of dye Pegringsingan in the village of Tenganan andthe plant characterize morphological and agronomic. The method used in this study wasexplorative and survey method. Implementation of the study consisted of three phases ofactivities, namely (1) the collection of secondary data, (2) surveys various plants natural dyeused for tenun pegringsingan and distribution, and (3) the identification of morphological andagronomic characters. The results showed there were four plant dyes for tenun pegringsingani.e sunti or noni (Morinda citrifolia) as a red dye, walnut (Aleurites moluccana (L.) Willd ) asa yellow dye, kepundung white or red (Baccaurea racemosa Var. white, Baccaurea racemosaVar. red), taum (Indigofera sp) producing a blue color.